Are European sovereign bond spreads in concordance with macroeconomic variables evolution?. Issue 1 (9th January 2017) - Sorrosal-Forradellas, M. Teresa; Martinez, Lisana B.; Terceño, Antonio
Abstract : Purpose: The last great financial crisis which arose in the middle of 2007 in the USA produced contagion effects over others economies. The purpose of this paper is focused on analyzing the evolution of a set of economic variables of 17 European countries since 1991 until 2013. Sovereign bond spreads are also considered to compare the incidence of the financial crisis over the economies considering macroeconomics fundamentals and fixed bonds. Design/methodology/approach: Self-organizing maps (SOMs) are used to achieve the purpose of the research. With this methodology, it is possible to analyze the evolution of the macroeconomic fundamentals of each country, obtaining particular and general conclusions according to the position of each country in the SOM. Moreover, the countries are compared between them and with its respective sovereign bond spreads level for each year of analysis. Findings: The impact of the crisis is different between the countries was analyzed. Belonging to the European Monetary Union is an interesting characteristic of some of the most affect economies. Research limitations/implications: This research presents wide implications for the economies to control the most vulnerable economic variables in front of financial crisis to prevent the contagion effect. The inclusion of more economic variables and countries could enhance the study. Originality/value: This research analyzes the relationship between macroeconomic variables and sovereign bond spreads using an infrequent methodology. The results obtained are valuable because they highlight how the present crisis has differently affected the European countries.